Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi di BEI - Tamba, Anggin Nurcahaya; Nadia Laras Br. Hutagalung (Politeknik Ganesha Medan, 2024)
The purpose of this study is to investigate and demonstrate how the non-cyclical consumer sector companies listed on the Indonesia stock exchange in 2021–2022 are affected in terms of profit growth by the current ratio, debt to equity ratio, total assets turnover, net profit margin, and return on assets. Additionally, investigate and assess how Company Size affects the relationship between Profit Growth and Current Ratio, Debt to Equity Ratio, Total Asset Turnover, Net Profit Margin, and Return on Assets in Indonesian Non-Cyclic Consumer Sector Businesses. Exchange of Stocks during 2021–2022. The population of this study comprises 113 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2021–2022 period, out of a sample of 95 companies. If a year of observation is added, there are 190 specimens total. Purposive sampling was the method of sampling that was employed in this study. Model feasibility tests, internal model tests, and external model tests are the analyses that are employed. According to the study's findings, profit growth is unaffected by the current ratio, debt to equity ratio, net profit margin, and return on assets. Profit growth is influenced by the quantity of raw materials used. Furthermore, a company's size has no bearing on the debt to equity ratio, return on assets with profit growth, net profit margin, total asset turnover, or current ratio.